FIVE THINKING MECHANISMS AS TECHNIQUES FOR DEVELOPING AN OUTLINE - Pana Pramulia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
A short story is a type of prose that does not have a lot of conflict and many characters in it, but it has a complex unanimity. However, writing a short story is not easy because it requires imaginative power and qualified creativity to express ideas and processing language. The imaginative process and creativity do not just exist but need to be trained intensively and continuously. There are several strategies for writing short stories, especially for beginner writers. The first strategy is compiling the outline of the essay, and the second one is using the technique of developing idea. One of the techniques to compile the outline of the essay is using “cilukba” pattern technique. Meanwhile, 5 thinking mechanisms is a technique used for developing an essay outline. This technique includes developing, omitting, increasing, decreasing, and sideways. This pattern was applied by PGSD students at Universitas PGRI Adi Buana registered in 2016 to write short stories. The methods included that (1) lecturers decided themes, (2) students were assigned to compile an outline based on “cilukba” patterns, (3) students were assigned to study the 5 thinking mechanism techniques, and (4) students were asked to arrange the outline based on the 5 thinking mechanism techniques. Based on this finding, PGSD students of Universitas PGRI Adi Buana Surabaya were able to write short stories and compiled the short stories into an ISBN collection book of short stories.